Metodologi Studi Islam dalam Menyikapi Kontradiksi Hadis (Mukhtalaf al-Hadits) - Syaripudin, Ahmad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
The Method of Islamic Studies in addressing the contradictions in the Hadith (Mukhtalaf Al-HadÄ«á¹¡). This article is aimed to explain The Method of Islamic Studies in addressing the contradictions in the Hadith (Mukhtalaf Al-HadÄ«á¹¡) by citing an example of a Hadith is considered contradictory, and the role of the ulama in explaining the Mukhtalaf Al-HadÄ«á¹¡.